PEMANFAATAN PERPUSTAKAAN SEKOLAH, KEBIASAAN BELAJAR HUBUNGANYA DENGAN HASIL BELAJAR SISWA KELAS V SD - Dian Resti Widiastuti; Budiman Tampubolon; Hery Kresnady (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze the use of the school library and study habits togetherin relation to the learning outcomes of grade V students of Elementary School 4Nyatang, Pinoh Utara District, Melawi Regency. This type of research isassociative research with quantitative descriptive methods and the form ofresearch is a correlation study. The population in this study amounted to 39students, the sampling technique was purposive sampling with 11 students. Datacollection techniques in research are indirect communication techniques anddocumentary study techniques. Data collection tools used were questionnaires andlearning outcomes documents. The results showed that the use of the school librarywas categorized as quite good at 81.82% and the study habits were categorized asquite good with 90.91%. Meanwhile, the student learning outcomes werecategorized as good at 45.45% and good enough for 54.55%. The results ofstatistical calculations using the product moment correlation formula forcalculating the use of the school library with learning outcomes obtained r countof 0.689. Meanwhile, for the calculation of students' learning habits and learningoutcomes, the r count was 0.705. For the calculation of multiple correlation, the rcount is 0.948 and the r table is0.602, then the significance test is carried out withthe F test, the result is=23, with 4.46.>or23>4.46. So the multiple correlationcoefficient found is significantKeywords: Use of School Libraries, Study Habits, Learning Outcomes